Exploring purchase intentions of new energy vehicles: From the perspective of frugality and the concept of "mianzi". (1st September 2019) - Chen, Kai; Ren, Chaoran; Gu, Rong; Zhang, Pingdan
Abstract: By incorporating socio-culture elements into cognitive behavior models, this study explored the influence of supportive policy and customer perceived value on customer purchase intentions of new energy vehicles, and probed the mediating effects of the frugality and the concept of "mianzi". In the current study, the construction of customer perceived value was divided into three dimensions: price factor, functional quality, and service quality. Based on 406 samples in the survey, the study applied structural equation modeling to test the hypotheses. The results showed that supportive policy not only directly influenced price factor and purchase intentions, but also had an indirect positive impact on customer purchase intentions through the mediating effect of the frugality. Meanwhile, three dimensions of customer perceived value had different influences on the purchase intentions. Price factor only affected customer purchase intentions directly, and functional quality only exerted indirectly positive effect through the mediating effect of the frugality on customer purchase intentions. Service quality significantly promoted the concept of "mianzi", while the concept of "mianzi" had no significant effect on customer purchase intentions of new energy vehicles.